Pengaruh Ekstrak Daun Harendong Bulu (Clidemia hirta) Terhadap Kadar Gula Darah Mencit (Mus Musculus) - Niza, Hairun; Marceilha, Nadia (JURNAL KESEHATAN TERAPAN, 2023)
Diabetes mellitus is a metabolic disease characterized by hyperglycemia due to beta cell damage orinsulin resistance. One of the plants used as medicine is harendong bulu (Clidemia hirta). HarendongBulu leaf with the Latin name (Clidemia hirta) is a plant that has been forgotten by its medicinalbenefits, namely diabetes mellitus. Harendong Bulu leaves contain secondary metabolites, namelyflavonoids and tannins. This research is an experimental research. The aim of this study was toinfluence the effect of Harendong Bulu (Clidemia hirta) leaf extract on alloxan-induced blood sugarlevels in mice. The research object was divided into 5 groups, namely the negative control group (NaCMC 0.5%), positive control (Metformin), the treatment of harendong bulu leaf extract at a dose of150 mg/kgBW, 300 mg/kgBW, 450 mg/kgBW. Blood sugar levels were measured on day 0 using aglucometer and on day 21 using a spectrophotometer. Data analysis using the two-way ANOVA testshowed that there was no significant difference in blood sugar levels between the treatment groups.The conclusion of this study is from statistical tests that the dose of Harendong Bulu leaf extract hasno significant effect on reducing blood sugar levels in mice induced by alloxan.